Impregnation of [Emim]Br ionic liquid as plasticizer in biopolymer electrolytes for EDLC application. (10th April 2021) - Asnawi, A.S.F.M.; Hamsan, M.H.; Aziz, S.B.; Kadir, M.F.Z.; Matmin, J.; Yusof, Y.M.
Abstract: A solid polymer electrolyte based on maltodextrin (MX) – methylcellulose (MC) – ammonium bromide (NH4 Br) was successfully prepared via the solution casting method by impregnating different amounts of [Emim]Br. Interaction of the electrolyte components was proven by the Fourier transmission infrared (FTIR) and X-ray diffraction (XRD) analyses. With the addition of 30 wt% [Emim]Br (L30), the conductivity was enhanced to (3.39 ± 0.22) × 10 −4 S cm −1 at room temperature. The L30 electrolyte achieved the lowest Ea value of 0.15 eV that obeyed the Arrhenius theory. Ionic conductivity was found to influence the ionic mobility ( μ ), number density ( n ) and diffusion coefficient ( D ), which was investigated using the EIS and FTIR methods. Dielectric analysis was further verified the conductivity trend and proved the non-Debye behavior. The electrolyte with 30 wt% [Emim]Br obtained the lowest Tg value of 68.91 °C. TGA/DTG results indicated that the electrolytes were thermally stable until ∼ 400 °C. The ions were the main charge carriers based on the TNM result. LSV measurement revealed that the L30 electrolyte decomposed at 1.56 V. In the fabricated EDLC, specific capacitance values were measured using CV and charge–discharge analyses where the values obtained were 9.85 F g −1 and 9.47 F g −1, respectively. Energy and power densities were stabilized in the range of 0.1–0.2 Wh kg −1 and 20–25 W kg −1, respectively as the EDLC completed the cycles.